To evaluate the analgesic activity of Ficus Racemosa leaf extract in albino mice using Eddy's hot plate method. - rai, Niket; Phadnis, Pradeep; Vyas, Savita (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective-To evaluate the analgesic activity of ficus racemosa leaf extract in albino mice and its comparison with standard drug using Eddy's hot plate method. Method-Chloroform leaf extract was obtained using soxhlet apparatus. Isolated fraction of extract (FRE) was used for the experiments. Swiss albino mice of either sex, average weight 20-25gms were used for experiments. Animals were divided into 6 groups consisting of 6 animals each. In hot plate method, Basal reaction time was recorded. Each group received particular treatment and reaction time was recorded after half, one, two and four hours. Pentazocine was taken as standard drug. Result-FRE at the dose of 50mg/kg did not shows any significant analgesic activity while at the dose of 100 and 200 mg/kg it showed significant analgesic activity as compare to control group. FRE at dose of 200mg/kg showed significant analgesic activity as compare to pentazocin. Pentazocin in combination with 50mg/kg dose of FRE produced significant analgesic activity when compared to control value or either treatment alone. Conclusion-FRE endowed with central analgesic properties in dose dependent manner. And also enhances the analgesic effect of pentazocin. However further study is needed in order to understand the precise mechanism. Keywords- ficus racemosa, analgesics, pentazocin, albino mice, Eddy's hot plate.